2017
DOI: 10.1111/inr.12391
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for people living with schizophrenia in Sub‐Saharan Africa: an adapted realist review

Abstract: Mental health services in Sub-Saharan Africa are limited by fiscal shortages, lack of mental health services and qualified mental health professionals. This review provides evidence to inform nursing and healthcare policy, including recruiting and training mental health professionals and ensuring access to evidence-based, person-centred and culturally relevant mental health services within the primary care context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…This finding is consistent with a recent review of 40 studies on schizophrenia from eight countries in Sub-Saharan Africa, which found that most people with CPD were treated by mainstream medical psychiatry and faith/traditional healers. 30 Although CAE is mostly a patient self-management approach and does not specifically focus at the provider level, there were some modifications made to the CAE curriculum that concerned providers. First, we included content on working with traditional healers, so as to minimise an adversarial stance, as well as with providers that are embedded in many Tanzanian communities.…”
Section: Refining Cae-l For the Tanzanian Settingmentioning
confidence: 99%
“…This finding is consistent with a recent review of 40 studies on schizophrenia from eight countries in Sub-Saharan Africa, which found that most people with CPD were treated by mainstream medical psychiatry and faith/traditional healers. 30 Although CAE is mostly a patient self-management approach and does not specifically focus at the provider level, there were some modifications made to the CAE curriculum that concerned providers. First, we included content on working with traditional healers, so as to minimise an adversarial stance, as well as with providers that are embedded in many Tanzanian communities.…”
Section: Refining Cae-l For the Tanzanian Settingmentioning
confidence: 99%
“…The study procedures outlined above are intended to pave the way for being able to implement a large-scale intervention trial for CPD in the Tanzanian setting. A recent review of treatments for schizophrenia in SSA by Chidarikire and colleagues (Chidarikire et al., 2018) highlighted the limited mental health services related to financial constraints, lack of qualified mental health professionals and problems in care access. In the review by Chidarikire, 40 studies from eight countries demonstrated that most people with CPD were treated by both modern psychiatry and faith/traditional healers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent review of 40 studies on schizophrenia from eight countries in Sub-Saharan Africa found that most people were treated by both mainstream psychiatry and faith or traditional healers. 12 Much of the programme evaluation was short term and based on quantitative and qualitative assessment of process or proxy measures rather than mental health outcomes. To some extent, this was unavoidable given the time constraints of the Emerald programme, but may again limit generalisability.…”
Section: Generalisabilitymentioning
confidence: 99%